2008
DOI: 10.1111/j.1439-0310.2007.01447.x
|View full text |Cite
|
Sign up to set email alerts
|

Infanticide and Maternal Offspring Defence in European Rabbits under Natural Breeding Conditions

Abstract: Infanticide is an important source of mortality of dependent offspring in several mammal species, whereas female conspecifics are often the perpetrators. This has led to maternal counter‐strategies, such as the defence of the nests. However, cases of infanticide are hard to detect in the field, and studies on maternal offspring defence behaviour under natural breeding conditions are scarce. We conducted such a study on the European rabbit (Oryctolagus cuniculus), which is usually considered to show low materna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 37 publications
1
75
0
1
Order By: Relevance
“…Our results revealed that the habitat was not homogeneous and that the number of neighbours differed for individual females during the same year and season. Neighbours compete with each other, for example for access to food, but can also commit infanticide (Boonstra 1978;Hoogland 1985;Rö del et al 2008). Infanticide is regarded as one main reason for females of small mammals being territorial (Wolff 1993), and has also been observed in the striped mouse (field: Schradin & Pillay 2003;captivity: Schradin et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Our results revealed that the habitat was not homogeneous and that the number of neighbours differed for individual females during the same year and season. Neighbours compete with each other, for example for access to food, but can also commit infanticide (Boonstra 1978;Hoogland 1985;Rö del et al 2008). Infanticide is regarded as one main reason for females of small mammals being territorial (Wolff 1993), and has also been observed in the striped mouse (field: Schradin & Pillay 2003;captivity: Schradin et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Relationships among females usually stabilize and aggression becomes ritualized once a rank order is established (Mykytowycz and Rowley, 1958;von Holst et al, 2002), and bonding among female kin can help in stabilizing the social structure within a female group (Rödel et al, 2008c). However, group territories in wild rabbits are large (in a field enclosure study, 0.05-0.7 ha; Rödel et al, 2008b), and animals can avoid and escape aggressive encounters. This does not appear to accord with animal welfare recommendations (e.g.…”
Section: Housingmentioning
confidence: 99%
“…This means that they cannot fight and wound each other at the time of the reproductive cycle they are most likely to do so. Also, they cannot kill or wound each other's litters when these are still very young, immobile and vulnerable (a behaviour observed both in wild (Kunkele, 1992;Rodel et al, 2008) and commercial breeding rabbits (Szendro and Mcnitt, 2012)). However, postgrouping aggression and wounding are still common in these semi-group systems Rommers et al, 2014).…”
Section: Introductionmentioning
confidence: 99%